The Digital Transformation Of Islamic Education In The Perspective Of ‎Abraham Maslow's Hierarchy Of Needs - Muhammad Zainal Abiin; Zarkoni; Hasan Baharun (cendekia citra gemilang, 2026)
This study aims to analyze the digital transformation of Islamic education from the perspective of Abraham Maslow’s Hierarchy of Needs and to understand its implicationsfor fulfilling students’ humanistic needs in the digital era. The research employed a qualitative approach with a library research method by examining various literature related to the digitalization of Islamic education and Maslow’s Hierarchy of Needs theory. Data were analyzed using content analysis through data reduction, categorization, interpretation, and conclusion drawing. The findings reveal that the digital transformation of Islamic education contributes positively to fulfilling students’ physiological and safety needs through easier access to learning, flexibility of time and space, and more structured digital learning systems. Furthermore, digitalization also supports students’ self-actualization through the development of creativity, digital literacy, critical thinking skills, andindependent learning. However, digital transformation also creates challenges for social needs and humanistic values due to reduced direct interaction, emotional closeness, and social relationships between teachers and students. Therefore, the digital transformation of Islamic education should be developed in a balanced manner by positioning technology as a supporting instrument that remains oriented toward holistic human development so that the social, spiritual, and humanistic values of Islamic education can be maintained.